SWOT analysis in the implementation of the independent curriculum at kindergarten - Salisa, Iklina Helma (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: One of the most significant educational reforms in Indonesia is the Merdeka Curriculum. However, despite its potential, many teachers, particularly in kindergarten settings, still face challenges in its implementation and require further understanding of Merdeka Curriculum-based learning. This study explores the implementation of the Merdeka Curriculum in Muslimat NU Diponegoro 81 Kranggan Kindergarten. Methods: This research employs a qualitative descriptive method with SWOT analysis framework was used to evaluate internal and external factors affecting curriculum implementation. Findings: The SWOT analysis reveals that the implementation of the Merdeka Curriculum at Muslimat NU Diponegoro 81 Kranggan Kindergarten is relatively effective, supported by several strengths such as a strategic location, well-qualified teachers, strong teacher collaboration, adequate learning facilities, and active student participation. However, challenges remain, including a lack of teaching materials, limited teacher training, and varying student skill levels. Opportunities include strong support from student guardians and the Muslimat foundation, while threats involve insufficient understanding of the curriculum among parents, financial constraints, and limited periodic supervision by Muslimat administrators. Conclusions: The study concludes that the successful implementation of the Merdeka Curriculum depends on the collaboration between school leaders, teachers, and external stakeholders. While internal strengths and external opportunities facilitate implementation, challenges such as financial limitations, lack of training, and inconsistent supervision need to be addressed. To enhance curriculum implementation, principals should strengthen leadership and external partnerships, teachers should participate in continuous training, and policymakers should provide clearer guidelines and financial support. Novelty/Originality of this Article: This study contributes to the understanding of early childhood education curriculum reform by offering a practical SWOT analysis of the Merdeka Curriculum in kindergarten settings. Unlike previous studies, it provides a structured evaluation of implementation challenges and strategies for improvement, serving as a valuable reference for educators, school administrators, and policymakers in Indonesia.